Survival with Technology: Elderly Teachers’ Perspective Towards Emergency Online Learning During the COVID-19 Pandemic in the Philippines - Faramarz Samifanni; Rose Leslie R Gumanit (Studies in Learning and Teaching, 2021)
This study analyzed the content of YouTube news clips on elderly teachers concerning emergency online learning during the COVID-19 pandemic. Using traditional content analysis, the included news videos were transcribed, interview segments were translated and familiarized, dominant words were identified, data were coded, categorized, and themed. Four dominant words were highlighted: online, students, teachers, and pandemic. Three themes on technical challenges and support needs, health issues, and resilience emerged in the analysis. Results show that elderly teachers are persistent to adapt to emergency online learning despite the struggles they are facing. The analysis also highlights the negative effects of the sudden shift to emergency online learning on the physical and psychological health of elderly teachers. Furthermore, the elderly teachers, are ensuring students’ access to education even at their own cost. Implications to the country’s quality of education and suggestions of providing better technical and psychological health support to elderly teachers were presented.